Climbing the Ladder in Crafting A Professionalism Framework for Nursing Students in South Africa - Bimray, Portia; Jooste, Karien (Babali Nursing Research, 2023)
Introduction: Globally, higher education institutions are faced with training nursing students to meet the healthcare demands of an ever-changing society. In nursing education, innovative ways are essential to instil professionalism among nursing students to prepare them for managing complex practice issues without compromising the professional standards of nursing. This paper concentrates on developing a conceptual framework, for the facilitation of professionalism among undergraduate nursing students at a higher education institution in South Africa. Methods: This study was a constructive paradigm research with qualitative descriptive approach. Data was collected by focus group interviews with participants (three cases). Different phases were followed in the framework development using the case method. In Case 1, focus groups (n=8) were held with student nurses from each of the levels of a four-year degree program (n=42). In Case 2, focus groups (n=3) and unstructured interviews (n=1) were conducted with purposively selected nurse educators (n=20), representing academics and clinical facilitators. Case 3 comprised of semi-structured individual interviews (n=5) and focus groups (n=5), a total of 29 preceptors in professional practice. An analysis of a within-case followed by cross-case data analysis, resulted in merged themes of three cases that emerged as an overall case study. Results: Actual accounts of the participants` experiences on nursing professionalism during theory and practice education were captured in the six concepts of the Practice Orientated Theory that structured the developed framework. Conclusion: A logical methodological description of creating a framework on nursing professionalism was outlined and the conceptual framework can be evaluated for transferability to other similar nursing education training environments.